2018
DOI: 10.1002/mp.13284
|View full text |Cite
|
Sign up to set email alerts
|

Cycle‐consistent adversarial denoising network for multiphase coronary CT angiography

Abstract: Purpose In multiphase coronary CT angiography (CTA), a series of CT images are taken at different levels of radiation dose during the examination. Although this reduces the total radiation dose, the image quality during the low‐dose phases is significantly degraded. Recently, deep neural network approaches based on supervised learning technique have demonstrated impressive performance improvement over conventional model‐based iterative methods for low‐dose CT. However, matched low‐ and routine‐dose CT image pa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
164
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 198 publications
(164 citation statements)
references
References 29 publications
0
164
0
Order By: Relevance
“…In image reconstruction of moving organs, paired training samples are hard to obtain. Therefore, Ravì et al (2018) proposed a physical acquisition based loss to regulate the generated image structure for endomicroscopy super resolution and Kang et al (2018) proposed to use CycleGAN together with an identity loss in the denoising of cardiac CT. Wolterink et al (2017b) found that in low dose CT denoising, meaningful results can still be achieved when removing the image domain fidelity loss from the pix2pix framework, but the local image structure can be altered. Papers relating to medical image reconstruction are summarized in Table 1.…”
Section: Reconstructionmentioning
confidence: 99%
“…In image reconstruction of moving organs, paired training samples are hard to obtain. Therefore, Ravì et al (2018) proposed a physical acquisition based loss to regulate the generated image structure for endomicroscopy super resolution and Kang et al (2018) proposed to use CycleGAN together with an identity loss in the denoising of cardiac CT. Wolterink et al (2017b) found that in low dose CT denoising, meaningful results can still be achieved when removing the image domain fidelity loss from the pix2pix framework, but the local image structure can be altered. Papers relating to medical image reconstruction are summarized in Table 1.…”
Section: Reconstructionmentioning
confidence: 99%
“…Another way is to build algorithms that do not require a training set, or, at least, not a paired training set (i.e., measurements and their corresponding reconstructions). One way to do this is by enforcing cycle consistency [102], where a pair of algorithms are built, one for reconstruction and one for simulating data. These algorithms are trained together from unpaired data such that they are inverses.…”
Section: Where To Get the Training Datamentioning
confidence: 99%
“…Cycle-GAN is another unsupervised translation approach which is based on the combination of adversarial losses and the pixel-wise cycle-consistency loss [24]. It has been adapted for medical translation tasks such as CT to MR bidirectionaltranslation [25] and CT denoising [26]. Other unsupervised frameworks exist with an overview available in [27].…”
Section: Introductionmentioning
confidence: 99%